The role of commitment as a moderator of the influence of financial literacy on the sustainability of MSME Businesses in the Kenjeran Area of Surabaya - Juliani Pudjowati; Susi Tri Wahyuni; Eryana Setyarti (Institute of Accounting Research and Novation (IARN), 2025)
The purpose of this study is (1) To examine the influence of financial literacy on the sustainability of MSME businesses. (2) To analyze the role of commitment as a moderator of the relationship between financial literacy and the sustainability of MSME businesses. The research method used is quantitative descriptive research. The population in this study were all MSME actors in the Kenjeran area of ​​Surabaya, totaling 219 people. While the research sample used the Slovin formula with a standard error of 5% of 141 respondents. The data analysis technique used in this study was path analysis using the SPSS program. The results of this study indicate that there is a significant direct influence between financial literacy and the sustainability of MSME businesses in the Kenjeran area, Surabaya, and that the commitment of business actors plays a role in strengthening (moderating) the relationship.